Tuesday

September 30, 2014

September 30, 2014

Posted by **Lance** on Monday, May 5, 2014 at 4:20pm.

f(x) = e^(4x+2) - 10

- Algebra, Logirithms -
**Steve**, Monday, May 5, 2014 at 6:18pmy = e^(4x+2) - 10

y+10 = e^(4x+2)

4x+2 = ln(y+10)

x = (ln(y+10)-2)/4

so, f^-1(x) = (ln(x+10)-2)/4

**Answer this Question**

**Related Questions**

algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...

College Algebra - Find the inverse of the function below. Graph the function ...

math - The cost of producing q articles is given by the function C=f(q)=100+2q...

Algebra - I have to find the inverse function of f(x)=3-4x. I got y=3-x/4 for ...

Algebra - Myra uses an inverse variation function to model the data for the ...

Algebra - T o convert from X degrees centigrade to y degrees fahrenheit the ...

pre calculus - Find the inverse of the function below. Graph the function below ...

Algebra 2 - Find the inverse of the following function: f(x) = 3x + 12 I don't ...

precalculus - Find the inverse of the function below. Graph the function below ...

Maths B - (a) What is the inverse of the function y = 3x2 ? (b) On the same set ...